SS-OCT-derived morphometric changes in the choroid in patients with age-related macular degeneration - Peretiahina, D.O.; Ulianova, N.A. (Ukrainian Journal of Ophthalmology, 2025)
Background: Since the prevalence of late age-related macular degeneration (AMD) is increasing, investigating the role of the choroid in the pathogenesis of the disease is particularly important. Purpose: To examine swept-source optical coherence tomography (SS-OCT)-derived subfoveal choroidal thickness (SFCT) in patients differing in phenotypic manifestations of AMD. Material and Methods: Fifty-five AMD patients (67 eyes; age, 64 to 75 years) and 8 comparably matched-aged healthy controls (13 eyes) underwent SS-OCT measurement of SFCT. They were divided into 6 groups: healthy individuals without signs of AMD and patients with drusen; type 1 choroidal neovascularization (CNV); serous retinal pigment epithelium (RPE) detachment; type 1 CNV; and geographic atrophy (GA). Statistical analyses were conducted using Statistica software, version 13.5.0.17. Both parametric and non-parametric techniques were used. Results: Mean SFCT in patients with GA was 47.8% lower than in controls, 45.7% lower than in patients with drusen, and 51.7% lower than in patients with type 1 CNV (p < 0.05). We found no significant difference in mean SFCT between patients with GA and those with RPE detachment, or between the former and those with type 2 CNV. Patients with AMD and age-matched healthy controls were divided into four clusters based on choroidal thickness (cluster I, 105 ± 4.8 ?m; cluster II, 188 ± 3.5 ?m; cluster III, 266 ± 4.6 ?m; and cluster IV, 408 ± 14.9 ?m). There was no difference in cluster distribution between eyes with type 1 CNV and normal age-matched eyes. Of the eyes with drusen, most (81.8%) were from cluster II. A statistically significant majority of eyes with serous RPE detachment, type 2 CNV, and dry AMD were assigned to clusters I and II (p < 0.05). Conclusion: Patient groups differing in phenotypic manifestations of AMD were found to differ in the mean magnitude of SS-OCT-derived SFCT, and could be classified into 4 clusters on the basis of their value of SFCT.